Adoption and Implementation of Corporate Sustainability Strategy: Evidence from a Mixed Method Study - Mohamed Mihilar, Mohamed Shamil (Curtin University, 2017)
This study analyses the factors affecting the adoption and implementation of corporate sustainability strategy using a mixed method design in a developing economy context. The study contributes to the knowledge of how various external and internal factors explored in the study affected the adoption and implementation of corporate sustainability strategy. However, there was no evidence to suggest that the corporate sustainability strategy would improve financial performance.